2010
DOI: 10.1152/japplphysiol.01422.2009
|View full text |Cite
|
Sign up to set email alerts
|

Phrenicotomy alters phrenic long-term facilitation following intermittent hypoxia in anesthetized rats

Abstract: Sandhu MS, Lee KZ, Fregosi RF, Fuller DD. Phrenicotomy alters phrenic long-term facilitation following intermittent hypoxia in anesthetized rats. J Appl Physiol 109: 279 -287, 2010. First published April 15, 2010 doi:10.1152/japplphysiol.01422.2009 can induce a persistent increase in neural drive to the respiratory muscles known as long-term facilitation (LTF). LTF of phrenic inspiratory activity is often studied in anesthetized animals after phrenicotomy (PhrX), with subsequent recordings being made from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
0
18
1
Order By: Relevance
“…However, this absence was likely due to uncontrolled CO 2 which was decreased in all of the aforementioned studies. In support of this, PA has been observed in most studies in which isocapnia was maintained (141, 214, 232, 345, 346, 348, 398). …”
Section: Physiological and Molecular Responses To Episodic Hypoxic Exmentioning
confidence: 58%
“…However, this absence was likely due to uncontrolled CO 2 which was decreased in all of the aforementioned studies. In support of this, PA has been observed in most studies in which isocapnia was maintained (141, 214, 232, 345, 346, 348, 398). …”
Section: Physiological and Molecular Responses To Episodic Hypoxic Exmentioning
confidence: 58%
“…A final comment is warranted regarding postural impacts on diaphragm function. Similar to prior reports (9,14,15,17,41), rats were studied in the supine position to provide suitable access to the trachea and phrenic nerves. Studies in humans have clearly demonstrated that posture can impact diaphragm function.…”
Section: Discussionmentioning
confidence: 99%
“…Axotomy can trigger neuronal depolarization (33) and increases in phrenic nerve activity (42). However, axotomy effects should be limited to ipsilateral phrenic motoneurons with limited, if any, impact on contralateral motor pools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations